Guerra, intercambio y desplazamiento de los matsigenka nanti del Alto Camisea y Alto Timpía - Martha Rojas Zolezzi (Bulletin de l'Institut Français d'Études Andines)
In this essay, we review the war during the 1970s among of the Nanti nomads, a sub-section of the Matsigenka (pre-Andean Arawak) of the Alto Camisea and Alto Timpía in the Bajo Urubamba basin in the Upper Peruvian Amazon. This conflict dispersed and displaced them from their transhumance zones and led to the formation of new villages. After an introduction about the mythical origins of the war between the Matsigenka Nanti, we trace the process of displacement of a group of the matsigenka from the lower course of the Camisea River as a consequence of the violence of the rubber period to the area of the Alto Camisea and Alto Timpía rivers. As a result, they merged with another Arawak population and this led to the emergence of the current Nanti. Next, we analyze the factors that produced intra-tribal war among the Nanti population. Finally, we offer an interpretation of this war, in which the exchange played a central role, and the process of the displacement and shift to a sedentary lifestyle by the survivors of this indigenous people from the headwaters of the Alto Camisea and Alto Timpía rivers to the territory of the current Reserva Territorial del Estado. This affected ethnic groups that had isolated themselves voluntarily and it led to initial contact with Kugapakori, Nahua, Nanti y others (RTKNN).